Evaluation of doctors performance as facilitators in basic medical science lecture classes in a new Malaysian medical school - Salwani, Ismail; Mainul, Haque; Nor Iza, A.Rahman (2015)
Background: Didactic lecture is the oldest and most commonly used method of teaching. In addition, it is considered one of the most efficient ways to disseminate theories, ideas, and facts. Many critics feel that lectures are an obsolete method to use when students need to perform hands-¬on activities, which is an everyday need in the study of medicine. This study evaluates students' perceptions regarding lecture quality in a new medical school. Methods: This was a cross¬-sectional study conducted of the medical students of Universiti Sultan Zainal Abidin. The study population was 468 preclinical medical students from years 1 and 2 of academic year 2012–2013. Data were collected using a validated instrument. There were six different sections of questions using a 5¬ point Likert scale. The data were then compiled and analyzed, using SPSS version 20. Results: The response rate was 73%. Among 341 respondents, 30% were male and 70% were female. Eighty ¬five percent of respondents agree or strongly agree that the lectures had met the criteria with regard to organization of lecture materials. Similarly, 97% of students agree or strongly agree that lecturers maintained adequate voices and gestures. Conclusion: Medical students are quite satisfied with the lecture classes and the lectures. However, further research is required to identify student-centered teaching and learning methods to promote active learning.